RECENT TRENDS IN THE USE OF TECHNOLOGY IN EARLY CHILDHOOD LEARNING - Dela Safira Safira; Fitria Harahap (Proceeding International Seminar of Islamic Studies, 2023)
Technological developments have affected all aspects, especially in the field of education. It also stimulates teachers to use learning technology in teaching and learning activities. Therefore, this study aims to examine the use of technology, especially educational technology in teaching activities in PAUD. The research method used is a descriptive qualitative procedure. Data collection techniques used were observation and interviews involving 5 parents of students. Data analysis includes the stages: collection, reduction, display, and drawing conclusions. The results of previous research studies state that the forms of technology applied in learning vocabulary are learning tools which include video games, AR, tablets, and applications made by researchers with the aim of improving vocabulary learning. Furthermore, in terms of the application of learning resources, YouTube is a learning resource used in learning vocabulary, namely foreign languages. Which shows the importance of digital literacy for early childhood and parents in training children's intelligence, psychologically, language skills, cognitive, emotional, social, academic and critical, children's cognitive abilities increase and language skills get better and make it easier for parents to find content contains stories, pictures, songs, and others that are suitable for early childhood.